Intensifying tropical cyclone disasters in Northern China - Ying Li; Xin Zhang; Dajun Zhao; Shanshan Zhao; Peiming Dong (Environmental Research Communications)
Tropical cyclones (TCs) are rare but highly destructive in northern China, highlighting the importance of understanding their evolving impacts and associated disasters, especially given the region’s limited capacity for TC mitigation. This study investigates the spatiotemporal variations of TC-induced disasters in northern China from 2001 to 2020, with a focus on the impacts in terms of affected crop area, affected population, and direct economic losses (DELs). Results indicate that all three indicators increased during 2011–2020, underscoring the growing severity of TC-related disasters. Further analysis attributes this escalation to a notable increase in TC frequency, along with consistent upward trends in cumulative TC precipitation and TC-related extreme rainfall events over the same period. In particular, the frequency of extreme daily precipitation rose significantly in Heilongjiang, Jilin, Liaoning, and Shandong provinces, leading to greater societal and economic impacts across the region. This research highlights the growing risk of northern China to TC-induced hazards and emphasizes the need for more precise and regionally targeted disaster mitigation strategies.